Service user involvement in giving mental health students feedback on placement: A participatory action research study. (September 2015) - Speers, Janey; Lathlean, Judith
Summary: Background: Although the drive to engage service users in service delivery, research and education has mainstream acceptance, it is not easy to achieve meaningful involvement. The contribution that could potentially be made by users whilst accessing services is often overlooked. Objectives and Participants: This study involved stakeholders (mentors, service users and a lecturer) working together to design, evaluate and refine a system enabling students to seek feedback from service users. The feedback concerned mental health students' interpersonal skills and occurred whilst on practice placement. This research aimed to explore the experiences of those concerned when nine students attempted to learn from rather than about service users. Design: A 2-year study, encompassing five cycles of participatory action research (PAR). Setting: A small island community in the British Isles, adopting UK standards for pre-registration nurse education. Methods: Data came from interviews with service users and mentors and a series of reflective group discussions with students who volunteered to try out the feedback mechanism. The deliberations of the PAR stakeholder group informed the research cycles and added to the data, which were subject to thematic analysis. Findings: Findings indicated that service users volunteering to give feedback had unanimously positive experiences. Students' experience lay on a continuum: those with a stronger sense of self were more willing and able to ask for feedback than less confident students. Cultural adjustment to the role change needed was challenging, requiring self-awareness and courage. Over time, all students achieved deep learning and, for some, learning appeared transformative. Conclusion: Although contextual, the study concluded that the feedback initiative encouraged the development of more equitable relationships, in which mental health nurses respected the expertise of service users. This potentially benefits student development, recovery-orientated practice, service users and HEIs searching for meaningful ways to involve service users in learning and formative assessment. Highlights: Service users' reported feedback experiences were positive, without exception. Students' experiences of feedback were more ambivalent, but ultimately developmental. Service users' feedback can contribute to student learning and formative assessment. Mental health user feedback constitutes a good fit with recovery orientated practice. HEI user involvement policy can include users who students work with in practice.